Redox‐regulation of activator protein 1 family members in blood cancer cell lines exposed to cold physical plasma‐treated medium. Issue 12 (24th October 2016) - Schmidt, Anke; Rödder, Katrin; Hasse, Sybille; Masur, Kai; Toups, Lena; Lillig, Christopher H.; von Woedtke, Thomas; Wende, Kristian; Bekeschus, Sander
Abstract : Targeting cancer cells with cold physical plasma emerged as a promising application in plasma medicine. To understand its mode of action with regard to cellular redox‐regulation, two leukemia cell lines (Jurkat and THP‐1 cells) were plasma‐treated and their gene expression was compared. Transcriptomics revealed strikingly similar expression levels of activator protein 1 family members, and of a particular set of genes associated with apoptosis, DNA repair, and antioxidant defense. Interestingly, important constitutively expressed antioxidant transcripts were differently expressed in both cell types which suggest them to be crucial for the Jurkat's high and the THP‐1 cells' low sensitivity to plasma. Utilizing these targets as biological read outs may help rendering plasmas more effective against different types of cancers. Abstract : Activator protein 1 family members regulate gene expression which are important in redox signaling responses. Exposure to cold physical plasma‐treated medium significantly alters the expression of AP‐1 transcription factor subunits such as FOSB, JUND, and EGR1 in Jurkat and THP‐1 cells. These factors induce target gene expression of anti‐oxidant response, DNA repair, cell‐cycle progression, and apoptosis. Activation states of AP‐1 signaling cascades in plasma‐treated leukemia cells support potential of cold plasma in cancer therapy.